Phenotyping intake rate in dairy goats, a repeatable trait which can be measured automatically - Giger-Reverdin S.; Duvaux-Ponter C.; Friggens N.C. (Innovation for sustainability in sheep and goats, 2019)
In intensive systems, high producing animals are at risk of acidosis due to the high proportion of concentrates in their diet. There is considerable variability between individuals in occurrence and severity of acidosis which is likely related to feeding behaviour. Phenotyping this behaviour could explain some of the variation in digestive efficiency, and therefore in feed efficiency. Feeding behaviour was assessed at three periods (1st and 2nd lactations, 2nd gestation) on thirty-five contemporary goats. The evolution of feed intake during 15 hours after the afternoon allowance was measured individually every 2 min for 3 days. Two phenotypes were calculated: Q90 (quantity of diet consumed during the first 90 minutes post-feeding), P90 (Q90/quantity consumed during 15 hours). Intra-period individual repeatability was very high. The value for one period was highly correlated with that of a preceding one for P90, but poorly for Q90. Given this repeatability, it would be possible to characterise the feeding behaviour of all the goats during their first lactation and, in the following lactations, to restrict feed allowance of those with the highest P90 or Q90 in order to decrease the occurrence of acidosis in the herd, and thereby increase efficiency. These results on the variability of intake rate show that simple criteria to phenotype goats on intake rate can be applied in precision livestock farming systems.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)